(untitled) (Research, Society and Development, 2020)
Quarter Horse breed (QH) has been more recently used in sports in Northern Brazil, however it does not have yet biometric evaluation in order to compare to horses from other Brazilian regions, where QH has a larger historic. Therefore, the aim of our study was to assess and present the biometric profile of Quarter horse breed raised and used in sport activities (barrel racing and vaquejada) in the region of Manaus, AM, Brazil. For this purpose, eighty-two (82) QH, adults, were evaluated through photographs analyzed by the ImageJ® 1.46r software. Eight (8) linear morphometric measurements were performed per animal, namely: Withers height (WHe); Croup height (CrH); Codilho height (CoH); Body length (BL; Neck length (NL); Dorsal-lumbar length (DLL); Scapula length (SL) and Head length (HL). Our results were within the racial standard demanded by the Brazilian Quarter Horse Breeders Association, which demonstrates a racial standardization in the region. The animals were classified as having medium size, eumetric. Regarding the average values (in cm), we obtained: WHe of 147.53 (142.76 to 155.33), CrH of 147.38 (141.12 to 154.48), CoH of 83.13 (81.51 of 87.07), BL of 149.15 (147.20 to 152.70), NL of 57.12 (55.2 to 57.3), DLL of 54.94 (52.9 to 57.0) SL of 54.35 (53.4 to 55.20) and HL of 63.70 (62.20 to 64.60). Our findings suggest similarity between the animals of the Quarter Horse breed raised Manaus-AM region with animals from other Brazilian regions. as well as standardization within the required racial parameters. All animals showed good proportions for the barrel racing and vaquejada practices.